Presentation of knowledge sharing model in Bank Maskan Iran - Maryam Firoozi; ahmad vedadi; alireza Amirkabiri (ارزش آفرینی در مدیریت کسب و کار)
Abstract The purpose of this research is to present the knowledge sharing model in Maskan Bank of Iran. The research method is applicable in term of its purpose, and mixed in terms of implementation. The statistical population in the qualitative part includes 15 experts, professors, and all people who have had practical or research activities in the field of knowledge sharing, using a purposive sampling method; and in the quantitative part, it includes 344 employees of the headquarters of Maskan Bank of Tehran, using a simple random sampling method. Data collection was done in the qualitative part by using semi-structured interviews; and in the quantitative part by a researcher-made questionnaire. The data-based method was used in the analysis of the data of the qualitative part, and PLS software in the quantitative. The results in the qualitative part showed that 6 structures include: causal conditions (with 3 dimensions of universality and inevitability, the need to change the attitude towards branding, urban brand identity), contextual conditions (with 3 dimensions of brand structural coherence, urban branding, strategic location of city), intervening conditions (with 3 dimensions of tourist behavior pattern, investment/financing, environmental factors), dimensions of the phenomenon (with 3 dimensions of creating a platform for smart tourism, attention to stakeholders, integrated urban brand management), strategies (with 3 dimensions of urban advertising system improvement, smart urban branding design, urban brand culture), and consequences (with 3 dimensions of social capital development, development of quality of life, competitive power of urban brand). Based on the results of quantitative analysis, the relationships between significant research variables and the model have a good fit. Extended Abstract Introduction During many years and working in organizations, human resources acquire sets of ideas, thoughts, skills, experiences and applicable sciences. The collection of such reserves is considered the knowledge of each person, which is recorded in the person's mind over time. As long as this knowledge exists in a person's mind, other people do not have the ability to access and benefit from it. There are many organizations that have such people (Park & Gabbard, 2018). Leibovitz believes that knowledge management is a combination of acquisition and storage of obvious knowledge, along with intellectual capital management. In other words, knowledge management is the process through which organizations use their collected information. Approaches to knowledge management depend on the management perspective. Differences can be caused by information-based, technology-based, and culture-based perspectives (Asgharneghad & Haghdoust, 2022). Therefore, one of the most important means of continuous creation of knowledge is sharing it among all units and members of the organization with an emphasis on technology and social interaction, attention to which has an important role in the survival of the organization in the spaces facing the competitive organization (Gholipour domyeh, 2023). Knowledge sharing is the axis of development and transformation in different societies and it is considered the main focus of training specialized and trained human resources in any society. Realization of knowledge management, sharing and documenting it in financial and banking organizations is one of the basic needs of today's knowledge-oriented society. In the current age, which is called the age of knowledge, organizations are witnessing environments that are becoming more dynamic and challenging day by day, and consider intangible and spiritual capital, called knowledge, as an important and vital factor (Firouzi & Feyzi, 2017). Based on the said material, the researcher is trying to answer the question: what is the model of knowledge sharing in Iran Maskan Bank?